Pre-exercise carbohydrate and fat ingestion: effects on metabolism and performance - Hargreaves, M.; Hawley, J. A.; Jeukendrup, A. (Journal of Sports Sciences, 2004)
A key goal of pre-exercise nutritional strategies is to maximize carbohydrate stores, thereby minimizing the ergolytic effects of carbohydrate depletion. Increased dietary carbohydrate intake in the days before competition increases muscle glycogen levels and enhances exercise performance in endurance events lasting 90 min or more. Ingestion of carbohydrate 3-4 h before exercise increases liver and muscle glycogen and enhances subsequent endurance exercise performance. The effects of carbohydrate ingestion on blood glucose and free fatty acid concentrations and carbohydrate oxidation during exercise persist for at least 6 h. Although an increase in plasma insulin following carbohydrate ingestion in the hour before exercise inhibits lipolysis and liver glucose output, and can lead to transient hypoglycaemia during subsequent exercise in susceptible individuals, there is no convincing evidence that this is always associated with impaired exercise performance. However, individual experience should inform individual practice. Interventions to increase fat availability before exercise have been shown to reduce carbohydrate utilization during exercise, but do not appear to have ergogenic benefits.